Proto-Samoyedic and Proto-Manchu-Tungusic dwelling names an attempt at semantic reconstruction - Dybo, Anna (Anthropos)
Tungus-Manchu and Samoyed peoples inhabit adjacent territories and live in a similar environment since antiquity. Both of these language families also underwent divergence at roughly the same time. It is interesting to see which dwelling names can be reconstructed for the different proto-language states of these families, and with which ethnographically or archaeologically attested dwelling types these words can be correlated.